2014
DOI: 10.1116/1.4895840
|View full text |Cite
|
Sign up to set email alerts
|

Spatial location of the Ec-0.6 eV electron trap in AlGaN/GaN heterojunctions

Abstract: Deep trap spectra in AlGaN/GaN high electron mobility transistor (HEMT) structures were studied by capacitance deep level transient spectroscopy. A major trap with an ionization level near Ec-0.6 eV was detected and attributed to states in the GaN buffer close to the AlGaN interface. These states have a signature very similar to the previously reported traps in AlGaN/GaN HEMTs responsible for the device degradation under electric stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The 0.6 eV trap was similar to the trap pinning the Fermi level in the GaN:Fe buffer and could be associated with the main center in the buffer. However, the high sheet density of these traps on the order of 10 12 cm À2 suggests that we rather observed the accumulation of such traps near the AlGaN/GaN interface [187]. This accumulation was more prominent after oxygen annealing at 750-800 8C [186] (see Fig.…”
Section: Algan/gan Heterojunctions: the Origin Of Two-dimensional Gasmentioning
confidence: 91%
See 3 more Smart Citations
“…The 0.6 eV trap was similar to the trap pinning the Fermi level in the GaN:Fe buffer and could be associated with the main center in the buffer. However, the high sheet density of these traps on the order of 10 12 cm À2 suggests that we rather observed the accumulation of such traps near the AlGaN/GaN interface [187]. This accumulation was more prominent after oxygen annealing at 750-800 8C [186] (see Fig.…”
Section: Algan/gan Heterojunctions: the Origin Of Two-dimensional Gasmentioning
confidence: 91%
“…In MOCVD grown GaN:Fe buffers of the AlGaN/GaN HEMT structures, the two different states of that kind, one with the level near E c À0.59 eV and electron capture cross section of 3.3 Â 10 À13 cm 2 , the other at E c À0.6 eV and the electron capture cross section 6.8 Â 10 À15 cm 2 , could be clearly seen [186,187]. The latter trap pinned the Fermi level in the semi-insulating buffer as determined by PICTS that also showed the presence of a deeper center near E c À0.8 eV or E v +0.8 eV (PICTS cannot easily discriminate between the traps in the upper and lower half of the bandgap [186]).…”
Section: Fe Doping Effectsmentioning
confidence: 96%
See 2 more Smart Citations
“…In this device, both Tp1 and Tp2 have been found to be thermally activated with E a = 0.65eVand0.37eV, respectively. Traps with the similar levels have been reported and identified in the GaN buffer close to the interface (~0.6 eV) [29], in heterostructure's interface (0.642 eV) [30], in the GaN film (0.59-0.63 eV) attributed to the edge dislocations by DLTS [31], in AlGaN barrier layer (0.3 eV-0.54e V) detected from transconductance dispersion and admittance curves [26], and in the AlGaN layer (0.37 eV) based on dynamic on-resistance (NDR) [32], respectively. It was suggested that Tp1 in the GaN layer are close to the AlGaN/GaN interface [29][30][31].…”
Section: Detrapping Processesmentioning
confidence: 68%